INCREASING THE LEVEL OF WELFARE OF FAMILIES AS A FACTOR CONTRIBUTING TO THE ECONOMIC DEVELOPMENT OF UKRAINE (INNOVATIVE ECONOMY, 2025)
Zayukov I.V., Nikolina I.I. INCREASING THE LEVEL OF WELFARE OF FAMILIES AS A FACTOR CONTRIBUTING TO THE ECONOMIC DEVELOPMENT OF UKRAINEPurpose. The aim of the article is to generalize the results of sociological research on the level of well-being of Ukrainian families and to assess the relationship between self-assessment of the level of well-being of families and self-assessment of the economic situation of Ukraine.Methodology of research. In the process of studying the level of well-being, the method of analysis and synthesis was used; to study the relationship between the self-assessment of the level of well-being of families and the economic situation in the country, correlation-regression analysis was used; to visualize the results of the study, a graphical method was used.Findings. An analysis of the level of average wages in Ukraine for the period 1996−2024 as an important source of family income formation is conducted. The main results of sociological research on the material security of Ukrainian families in modern military conditions of the development of the Ukrainian economy are summarized. The structure of family incomes in Ukraine in modern military conditions is determined. A correlation and regression analysis is conducted to identify the relationship between the self-assessment of the level of family well-being and the economic situation in the country. Recommendations are developed to improve the level of well-being of Ukrainian citizens.Originality. Based on the application of mathematical modeling using correlation-regression analysis, it was found that respondents are more optimistic about the level of family well-being than the level of economic development, which encourages families in modern military conditions to rely more on their own strengths than on the prospects for the development of the domestic economy as a potential factor for increasing their incomes.Practical value. The results obtained potentially substantiate the thesis that the level of well-being of families in Ukraine depends not on the country’s economic development, but on their ability to optimize their own income, in particular by transitioning to the shadow economy, which can become the basis for making state management decisions in the system of effective management of citizens' incomes.Key words: income, salary, financial situation, economic development, analysis, regression.
Keywords: income; salary; financial situation; economic development; analysis; regression